Goat farming for livelihood improvement of tribal farmers at Gawandh tribal village of Maharashtra - DAS, S K; BHILEGAONKAR, K N; AITHAL, H P (The Indian Journal of Animal Sciences, 2022)
Livestock is an important integral part to the sustainability of economy of this nation and livelihood improvement of farmers, especially resource poor tribal farmers. Tribal Sub Plan (TSP) programme is a developmental programme of Government of India meant solely for the development of tribal area throughout India. So a pilot study was made at Gawandh tribal village of Peint taluka, Nashik, Maharashtra for the economic upliftment and livelihood improvement of tribal people with the object of overall development of tribal area. It was revealed that implementation of goat farming by 20 women tribal farmers at Gawandh tribal village, located at Nashik district of Maharashtra has benefitted tribal beneficiary immensefully. Survey report revealed that the average total income of the farmers at the beginning of the programme was ` 15,180 from all sources like agriculture, daily wage, but after four years of continuing this programme, tribal woman farmer on an average earned ` 50,565 from goat farming, besides 12 goats were remaining in their heard. So, income of tribal farmers has become more than triple in a period of four years through rearing of goat. Performance of Osmanabadi goat in the agro-climatic condition of Nashik was also good with high growth and twinning per cent (53.40%).